INKSPHERE INTEGRATED SMART GARMENT PRINTING IMPROVES PRODUCTION PERFORMANCE AND COMPETITIVENESS IN A RESOURCE-CONSTRAINED MICROENTERPRISE - Marji Marji; Erwin Komara Mindarta; Eddy Rudiyanto; Riana Nurmalasari; Muhammad Idris Effendi; Kintan Desinta (Community Development Journal : Jurnal Pengabdian Masyarakat, 2026)
Resource-constrained garment-printing microenterprises often operate with fragmented workflows, informal production records, and limited process control. This community-service implementation evaluated Inksphere, an integrated garment-printing system combining semi-automated rotary printing, conveyor transfer, controlled drying, standardized procedures, a production dashboard, workforce training, and digital customer tools. A before–after evaluation at JAEGR in Malang, Indonesia compared production, quality, delivery, workforce, resource, and business indicators. Batch time decreased from 360 to 235 minutes, daily capacity increased from 80 to 120 shirts, and product defects fell from 12.50% to 3.13%. On-time delivery increased from 68.00% to 88.64%, while rework, ink use, energy use, and unit production cost declined. Worker knowledge and procedural compliance also improved. The findings show that coordinated semi-automation, data visibility, and capability development can strengthen operational performance and competitiveness without requiring full factory automation.